Virtual Monuments and Memory:: an interdisciplinary and collaborative transnational experience in projection art - Oliveira, Andreia Machado; Almeida de Souza, Bárbara; dos Santos, Camila dos Santos; Augusto Alvim, Luiz; Zindela, Luyanda; Moreno dos Santos Camargo, Matheus (Revista Vazantes, 2020)
This article presents the interdisciplinary and collaborative artistic project “Virtual Monuments”, as a poetic research on projection art. Such project is a partnership between Brazil and South Africa, carried out based on audio and video records of the daily lives of the Brazilian cities of Santa Maria (RS) and Fortaleza (CE), and of the South African city of Durban. The artistic proposal is developed for dome projection, 360o panoramic screen and video mapping. The project problematizes notions of memory and monument, confronting official and imposing narratives at the expense of everyday life and daily ephemerality. In this sense, practices in art and technology become a space and a time of resistance and revitalization of other senses for life, under a contemporary look.